2021
DOI: 10.31616/asj.2020.0308
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Vestibular System on the Formation and Progression to Idiopathic Scoliosis: A Review of Literature

Abstract: The physiopathogenesis of adolescent idiopathic scoliosis remains unknown. However, a multifactorial pathogenesis is being assumed. Besides biomechanical, biochemical, and genetic factors, some studies have focused on congenital or acquired abnormalities in the vestibular organ with consecutive development of scoliosis. This study aims to analyze a possible correlation between any vestibular organ congenital or acquired pathologies and scoliosis based on the current literature. Therefore, we conducted a litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
(57 reference statements)
0
5
0
Order By: Relevance
“… 48 A relationship between vestibular system abnormalities and IS has also been reported. 49 These data suggest that patients with IS experience changes in system complexity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 48 A relationship between vestibular system abnormalities and IS has also been reported. 49 These data suggest that patients with IS experience changes in system complexity.…”
Section: Discussionmentioning
confidence: 94%
“…Proprioceptive deficits were reported in AIS patients in a recent review and meta-analysis article by Lau et al 48 A relationship between vestibular system abnormalities and IS has also been reported. 49 These data suggest that patients with IS experience changes in system complexity.…”
Section: Discussionmentioning
confidence: 94%
“…[ 52 ] Patients with AIS frequently exhibit kinematic abnormalities during walking, which can be attributed to the influence of vision, vestibular sensation, and somato proprioception. [ 53 ] A recent study discovered a correlation between the severity of scoliosis and a decrease in stride length among AIS patients. [ 54 ] In this study, subgroup analyses were conducted on selected spatiotemporal characteristic indices.…”
Section: Discussionmentioning
confidence: 99%
“…This view is supported by the early functional implementation of otolithic circuits, as shown in fish and amphibian larvae, and their impact on deformable skeletal elements during early ontogeny (Horn et al, 1986;Lambert et al, 2009Lambert et al, , 2013. Indeed, scoliotic deformations in humans are often accompanied by vestibular deficits (Manzoni and Miele, 2002;Hawasli et al, 2015;Scheyerer et al, 2020), demonstrated, e.g., by otolith endorgan-related impairments of cervical vestibular-evoked myogenic potentials in scoliotic patients (Pollak et al, 2013). A causal link between a unilateral vestibular loss and skeletal asymmetry has been confirmed in Xenopus laevis (Lambert et al, 2009).…”
Section: Introductionmentioning
confidence: 97%